Perbandingan Tingkat Pengetahuan Pencegahan Toksoplasmosis Pada Wanita Usia Subur di Kota Lhokseumawe - Abub Luthfi; Juwita Sahputri; Rizka Sofia (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Toxoplasmosis is a disease transmitted from animals to humans, caused by the protozoan parasiteToxoplasma gondii. The Toxoplasma gondii parasite has infected more than 60% of the world's population and2-51% in Indonesia. Women of childbearing age (15-45 years) are one of the risk groups for the transmission of infection by the Toxoplasma gondii parasite. A person's knowledge is influenced by various factors such as level of education, information, environment and culture. The purpose of this study was to compare the level of knowledge on prevention of toxoplasmosis in women of childbearing age in Lhokseumawe City. This research is a type of descriptive analytic research with a cross-sectional time approach. Samples were taken using a purposive sampling technique from women of childbearing age in Uteunkot Village and Kuala Meuraksa Village. The sample size was determined using the Snedecor & Cochran formula and the minimum sample size was 62 respondents in Uteunkot Village and 62 respondents in Kuala Meuraksa Village. The results of this study indicate that the majority of respondents in Uteunkot Village have a less knowledge level of 43.5% and the majority of respondents in Kuala Meuraksa Village also have a less knowledge level of 85.5%. Data analysis used the Mann-Whitney test. The results of statistical analysis showed a p value <0.05. The conclusion of this study is that there are differences in knowledge of toxoplasmosis prevention in women of childbearing age in rural villages and urban villages.